PENINGKATAN PEMAHAMAN MATERI MELENGKAPI CERITA MATA PELAJARAN BAHASA INDONESIA MELALUI STRATEGI GUIDED NOTE TAKING PADA SISWA KELAS IV MI MA’ARIF RANDEGANSARI DRIYOREJO GRESIK - Novianti, Ika (Journal Of Islamic Elementary School (JIES), 2017)
The background of this research is the problem of the low understanding of the material to complete the story in class IV students of MI Ma’arif Randegansari Driyorejo Gresik which is caused by learning activities that are less interesting and less involving students. So it is necessary to apply interesting strategies and can actively involve students. Guided Note Taking Strategy is a strategy that is applied through the process of reading, listening, memorizing and understanding information which is then poured into writing. The use of the Guided Note Taking strategy is expected to actively involve students’ activities. The formulation of the problem is how students’ understanding of the material completes the story of Indonesian subjects in class IV MI Ma’arif Randegansari before the Guided Note Taking strategy is applied? Then how is the implementation of the Guided Note Taking strategy in order to improve understanding of the material to complete the stories of Indonesian subjects in class IV MI Ma’arif Randegansari? Then how to increase the understanding of fourth grade students of MI Ma’arif Randegansari on the material to complete the story of Indonesian subjects after the Guided Note Taking strategy was applied?. This research method is a class action (Classroom Action Research). This CAR consists of two cycles, namely cycle I and cycle II. The cycle will be stopped when the specified performance indicator target has been achieved. The subjects in this study were fourth grade students of MI Ma’arif Randegansari Driyorejo Gresik with a total of 33 students consisting of 19 male students and 14 female students. Students’ scores on the daily test (pre-cycle) of the material for completing the story obtained an average value of 68 and the classical completeness was 39%, the average was still below the KKM set by the school, which was 78. The results showed the Guided Note Taking strategy in learning the material for completing the story. can be applied properly by researchers and have an impact on increasing students’ understanding of Indonesian subjects. The results of the observation of teacher activities in the first cycle obtained a final score of 73.8 and increased in the second cycle to 94.5. The results of the observation of student activities in the first cycle obtained a final score of 73 and increased in the second cycle to 93. The average score obtained by the students in the first cycle was 77 and increased in the second cycle to 88. The percentage of classical completeness in the first cycle was 51.5% and increased in the second cycle to 91%.